2007
DOI: 10.1098/rstb.2007.2093
|View full text |Cite
|
Sign up to set email alerts
|

Levels of processing during non-conscious perception: a critical review of visual masking

Abstract: Understanding the extent and limits of non-conscious processing is an important step on the road to a thorough understanding of the cognitive and cerebral correlates of conscious perception. In this article, we present a critical review of research on subliminal perception during masking and other related experimental conditions. Although initially controversial, the possibility that a broad variety of processes can be activated by a non-reportable stimulus is now well established. Behavioural findings of subl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
528
3
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 679 publications
(572 citation statements)
references
References 177 publications
(264 reference statements)
23
528
3
5
Order By: Relevance
“…It also fits with evidence that both task-1 and task-2 sets are simultaneously maintained in a dual-task setting, as indicated for example by the fact that the response time to task 1 is typically slower in a dual-task versus a single-task setting, independently of the inter-target lag (Jiang et al, 2004;Sigman and Dehaene, 2005). Our result also fits with previous observations that attention can influence the processing of unconscious stimuli (Koch and Tsuchiya, 2007;Kouider and Dehaene, 2007). For instance, the N400 elicited by an unconscious word during a dual-task vanishes if task 1 has a high perceptual load (Giesbrecht et al, 2007).…”
Section: Target Processing In a Dual-task Settingsupporting
confidence: 91%
See 1 more Smart Citation
“…It also fits with evidence that both task-1 and task-2 sets are simultaneously maintained in a dual-task setting, as indicated for example by the fact that the response time to task 1 is typically slower in a dual-task versus a single-task setting, independently of the inter-target lag (Jiang et al, 2004;Sigman and Dehaene, 2005). Our result also fits with previous observations that attention can influence the processing of unconscious stimuli (Koch and Tsuchiya, 2007;Kouider and Dehaene, 2007). For instance, the N400 elicited by an unconscious word during a dual-task vanishes if task 1 has a high perceptual load (Giesbrecht et al, 2007).…”
Section: Target Processing In a Dual-task Settingsupporting
confidence: 91%
“…Sensory information is processed in parallel and if the activity reaches a certain intensity threshold, it triggers the ignition of a network of brain areas including frontal, parietal and cingulate cortices Del Cul et al, 2007;Kouider and Dehaene, 2007;Sergent et al, 2005;Sergent and Dehaene, 2004). We propose that brain activations observed mainly in the frontal cortex but also in the parietal cortex between 400 ms and 600 ms (the M430 and M550 components), correspond to the ignition of the workspace linked to the conscious access to T2.…”
Section: Central Processing In Dual-tasksmentioning
confidence: 98%
“…The absence of an effect of a visible prime on the task set selection could be due to an excessively too short delay between the prime and the task cue in the conscious condition (16 ms) compared with the subliminal condition (83 ms). It has already been shown that the efficiency of visible primes generally increases as a function of the prime-target delay (Kouider & Dehaene, 2007). Two factors were therefore confounded: the visibility of the prime and the delay between prime and instruction.…”
Section: Introductionmentioning
confidence: 99%
“…Here, the presentation of an emotional face is immediately followed by a non-emotional picture (e.g. a photo of a neutral expression) which helps to block the awareness of the main stimulus of interest (see Kouider & Dehaene, 2007). Crucially, preventing awareness in this way is only possible if the emotional face is presented for a very short time, usually 10 to 30 milliseconds.…”
Section: Introductionmentioning
confidence: 99%